Monoclonal antibodies to the murine Ly-2.1 cell surface antigen. - Hogarth, P M (1982)
Six monoclonal anti-Ly-2.1 antibodies are described that arose from a single fusion using the spleen from a 129/ReJ mouse immunized with CBA/H thymus cells. The specificity was determined from the strain distribution, and testing of congenic strains where all six monoclonal antibodies detected the Ly-2.1 alloantigen. Furthermore, the antibodies fall into two groups: Group I (four antibodies) detected the expected number of Ly-2+ thymocytes and peripheral T cells, whereas Group II (two antibodies) detected 10% fewer peripheral T cells. Functional studies demonstrated that the Ly-2.1 determinant detected by a Group I antibody (49-31.1) was presented on cytotoxic T cells (Ly-1+2+), on concanavalin A (Con A)-induced suppressor T cells (Ly-1-2+), but absent from helper T cells (Ly-1+2-). One antibody (49-11.1) precipitated a 68,000-75,000 mol.wt glycoprotein, which on reduction yielded 30,000 and 35,000 mol.wt moieties. Thus, by functional, genetic and biochemical criteria these antibodies detected the Ly-2.1 specificity. In addition, a monoclonal, noncytotoxic, IgGl, anti-Thy-1.2 antibody is described.